2018
DOI: 10.1177/0017896918785928
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone messaging to promote uptake of HIV testing among migrant African communities in the UK

Abstract: Background: In the UK, African communities are a focus of public health efforts to increase uptake of HIV testing. Mobile phone interventions may be an innovative way of reaching migrant groups who are known to face multiple obstacles in accessing mainstream health services. This paper presents findings from a feasibility study that used participatory approaches to investigate the use of a text messaging intervention to encourage HIV testing among migrant African communities. Methods: Participants were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The risk of selection bias was also reported in the studies which utilised online surveys [ 29 , 49 , 92 , 97 ]. Online surveys have the potential to exclude respondents who lack internet access or technological proficiency, or who are wary of disclosing sensitive information online.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The risk of selection bias was also reported in the studies which utilised online surveys [ 29 , 49 , 92 , 97 ]. Online surveys have the potential to exclude respondents who lack internet access or technological proficiency, or who are wary of disclosing sensitive information online.…”
Section: Resultsmentioning
confidence: 98%
“…migrants to New Jersey were less likely to have residential telephones or may have "rapid turnover of telephone numbers" due to high residential mobility. The risk of selection bias was also reported in the studies which utilised online surveys [29,49,92,97]. Online surveys have the potential to exclude respondents who lack internet access or technological proficiency, or who are wary of disclosing sensitive information online.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Despite workplaces being a useful platform for health promotion, employers do not tend to include health testing in their health promotion offers, and when they do, this rarely, if ever, includes sexual health or HIV testing and awareness [45,46]. Only a small number of UK studies have reported on text messaging interventions aimed at raising awareness of HIV and increasing uptake of HIV testing (migrant African communities: Evans et al [47]) and only one of these was delivered through the workplace setting [48].…”
Section: Introductionmentioning
confidence: 99%